Factors associated with condom use negotiation by female sex workers in Bangladesh. (October 2013) - Alam, Nazmul; Chowdhury, Mahbub Elahi; Mridha, Malay K; Ahmed, Anisuddin; Reichenbach, Laura J; Streatfield, Peter Kim; Azim, Tasnim
Negotiation for condom use by female sex workers with their male clients can enhance condom use. A cross-sectional study was conducted among 1395 female sex workers; 439 from two brothels, 442 from 30 hotels, and 514 from streets of two cities in Bangladesh to determine the predictors of condom use negotiation. Consistent condom use rates in the 7 days prior to interview were reported to be 16.2%, 21.7%, and 4.5% among the brothel, hotel, and street-based female sex workers, respectively. Overall, 28.1% of female sex workers negotiated for condom use with their clients. Participation in behaviour change communication (BCC) programmes (AOR, 1.5; 95% CI, 1.2–2.0) and self-perceived risk of human immunodeficiency virus infection (AOR, 1.8 95% CI, 1.6–2.1) were positive predictors for condom negotiation. Compared to the hotel-based female sex workers, street (AOR, 0.6; 95% CI, 0.4–0.9) and brothel-based female sex workers (AOR, 0.7; 95% CI, 0.5–0.9) were less likely to negotiate for condom use. Female sex workers in Bangladesh are at high risk for sexually transmitted infection / human immunodeficiency virus infection because of low overall negotiation for condom use. Participation in BCC programmes had positive effect on condom negotiation by female sex workers, and should be strengthened in commercial sex venues.